Adverse drug reactions associated with amitriptyline - protocol for a systematic multiple-indication review and meta-analysis - Brückle, Maria-Sophie; Thomas, Elizabeth T.; Seide, Svenja; Pilz, Maximilian; González-González, Ana I.; Dinh, Truc Sophia; Harder, Sebastian; Glasziou, Paul; Gerlach, Ferdinand M.; Muth, Christiane (Systematic Reviews, 2020)
Unwanted anticholinergic effects are both underestimated and frequently overlooked. Failure to identify adverse drug reactions (ADRs) can lead to prescribing cascades and the unnecessary use of over-the-counter products. The objective of this systematic review and meta-analysis is to explore and quantify the frequency and severity of ADRs associated with amitriptyline vs. placebo in randomized controlled trials (RCTs) involving adults with any indication, as well as healthy individuals.